Cocoa Farmer Empowerment in Indonesia: Economic Gains, Social Impacts, and Power Dynamic - Damayanti, Riska; Mario, Mario; Amandaria, Riri (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2025)
Cocoa is one of Indonesia's key horticultural commodities with significant export potential, particularly in South Sulawesi. However, in recent years, cocoa production has declined due to land conversion, price fluctuations, limited access to agricultural inputs, and poor farming practices. This study examines the empowerment of cocoa farmer groups in Maliwowo Village, East Luwu Regency, to understand whether these interventions genuinely enhance farmers’ welfare or primarily serve corporate interests. Using a qualitative descriptive approach, this research draws on primary data from farmers and secondary data from government sources. Findings reveal that empowerment initiatives—led by the East Luwu Agriculture Office and PT Mars—have improved farmers' productivity, income, and access to resources through training, input provision, and financial support. However, these interventions also establish a subtle form of control over farmers' practices through knowledge dissemination and structured policies. Employing Michel Foucault’s theory of power and Anthony Giddens’ structuration theory, this study explores the interplay between institutional power and farmers' agency in shaping agricultural practices. While empowerment efforts enhance economic well-being by increasing yields, strengthening market networks, and improving social welfare through gender inclusion and access to capital, they also impose external expectations on farming practices. The study highlights the dual nature of empowerment: while it provides economic opportunities and social benefits, it also integrates farmers into a structured system that dictates best practices and compliance with global standards. Ultimately, sustainable cocoa production in Indonesia requires a balance between corporate, governmental, and farmer-driven initiatives to ensure long-term benefits for smallholder farmers while preserving their autonomy.